Проблеми і потенційні можливості розвитку ІТ-сфери в Україні за умов активізування процесів інтегрування до міжнародного ринку: управлінський аспект - Завербний, А.С.; Пушак, Я.Я. (Вісник економічної науки України, 2022)
Стаття присвячена проблемам, потенційним можливостям розвитку ІТ-сфери в Україні за умов активізування процесів інтегрування до міжнародного ринку. Проаналізовано тенденції кількості суб’єктів господарювання ІТ-сфери за останні роки. Стаття містить характеристику тенденцій розвитку та інституціональних суб’єктів регулювання світового ІТ-ринку за управлінськими рівнями. Проаналізовано стратегічні напрямки розвитку національного ІТ-ринку, що мають логічно узгоджуватися із головними сферами економіки. The article is devoted to the problems, potential opportunities for the development of the IT sphere in Ukraine under the conditions of the activation of the processes of integration into the international market. The trends in the number of business entities in the IT sphere in recent years have been analyzed. The article contains a description of development trends and institutional subjects of regulation of the global IT market by management levels. The strategic directions of the development of the national IT market, which should be logically consistent with the main areas of the economy, have been analyzed. Potential scenarios of the development of events on the domestic IT market are highlighted.
Modern information technologies make it possible to find effective solutions that improve business operations and are manifested quantitatively and qualitatively: the number of services, the cost of IT services and the level of reliability, the speed of bringing new services to the market or creating new conditions for existing ones. This happened thanks to the expansion of the domestic market, the need to export IT services, the improvement of the level of effectiveness of legal regulation of this area, which is taking place, in particular, with the wide involvement of business associations, public associations, etc.
One of the most promising and realistic scenarios is the consolidation and integration of the Ukrainian IT market with the EU market. It will contribute to the active development of the domestic IT market in Ukraine through the creation and implementation of new projects.
Cooperation of the IT industry with the state, promotion and stimulation of the development of this sphere by the state is necessary. For further growth and development of the domestic IT industry, the following measures are necessary: formation of a stable fiscal policy for the industry, elimination of regulatory barriers, promoting the activation of the development of IT education, raising the level of qualification of IT personnel, etc.